2019
DOI: 10.1177/2325967119s00280
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Extra-Articular Tenodesis Reduces Failure of Hamstring Tendon Autograft ACL Reconstruction -Two Year Outcomes from the STABILITY Study Randomized Clinical Trial

Abstract: Objectives: Persistent anterolateral rotatory laxity following anterior cruciate ligament reconstruction (ACLR) has been correlated with poor outcome and graft failure. We hypothesized that anterolateral complex reconstruction by way of a Lateral Extra-articular Tenodesis (LET) in combination with single bundle ACLR would reduce the risk of persistent rotatory laxity in young individuals who are deemed as being at high risk of failure. Methods: This is a pragmatic, multicenter, randomized clinical trial compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
179
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(194 citation statements)
references
References 0 publications
6
179
0
9
Order By: Relevance
“…The addition of lateral extra-articular augmentation procedures in combination with ACL reconstructions have yielded encouraging early results in adults, including significantly lower graft failure rates without compromising subjective patient outcomes. 10 , 16 These procedures have garnered particular interest in high-risk patient populations, including pediatric patients, those with a high grade pivot shift, patients with soft-tissue grafts with open physes, generalized ligamentous laxity, those undergoing revision ACL reconstruction, and high-level athletes participating in a sport that requires pivoting. Recent studies have reported that isolated ACL reconstructions in pediatric athletes have a 10% to 25% graft re-rupture rate, with less than 70% of patients reported to return to sport.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The addition of lateral extra-articular augmentation procedures in combination with ACL reconstructions have yielded encouraging early results in adults, including significantly lower graft failure rates without compromising subjective patient outcomes. 10 , 16 These procedures have garnered particular interest in high-risk patient populations, including pediatric patients, those with a high grade pivot shift, patients with soft-tissue grafts with open physes, generalized ligamentous laxity, those undergoing revision ACL reconstruction, and high-level athletes participating in a sport that requires pivoting. Recent studies have reported that isolated ACL reconstructions in pediatric athletes have a 10% to 25% graft re-rupture rate, with less than 70% of patients reported to return to sport.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 Although the specific indications for the use of these procedures are controversial, recent literature has reported that this surgical augmentation significantly reduces the risk of ACL reconstruction failure. 10,11 In a randomized control trial, primary ACL reconstructions with a hamstring autograft had a 2-year failure rate of 11%, whereas ACL reconstructions with a combined LET (modified Lemaire technique) had a 4.5% failure rate without any difference in subjective patient-reported outcomes. 10 Biomechanical studies have shown that both of these anterolateral complex procedures significantly reduce internal tibial rotation and anterolateral rotary instability, and when combined with ACL reconstructions, are able to restore anterior tibial translation to comparable amounts seen in native, healthy knees.…”
mentioning
confidence: 99%
See 3 more Smart Citations